How many 24-hour recalls or food records are required to estimate usual energy and nutrient intake? Quantos recordatórios de 24-horas ou registros alimentares são necessários para estimar o consumo usual de energia e nutrientes? - Rosângela Alves Pereira; Marina Campos Araujo; Taís de Souza Lopes; Edna Massae Yokoo (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2010)
For dietary intake assessments, one needs to know the minimum 24-hour recall or food record replications that are required to estimate usual energy and nutrient intake and to classify subjects correctly according to their nutrient intake. Data from two different studies on dietary intake that were carried out with 300 adults and 169 adolescents in the Rio de Janeiro Metropolitan area, Brazil, were analyzed. To estimate the number of replications two methods were applied: one based on the variances ratio, the other based on the within-subject variance alone. The most important results found were the requirement for 14 replications for boys and men, 15 for girls, and 23 for women in order to estimate energy intake with a precision of 90%. Also four replications for boys and seven for men, girls and women are required to classify individuals' energy intake with a correlation coefficient of 0.9. Due to the within variance in food intake, a larger number of replications is required to obtain estimates of usual intakes than is needed to classify subjects according to levels of dietary intake. Na avaliação da dieta é preciso conhecer o mínimo de replicações de recordatórios de 24 horas e de registros alimentares necessários para estimar o consumo usual ou para classificar indivíduos em categorias de consumo. Foram analisados dados de dois diferentes estudos desenvolvidos na área metropolitana do Rio de Janeiro, Brasil, com 300 adultos e 169 adolescentes. Para estimar o número de replicações foram aplicados dois métodos: um baseado na razão das variâncias e outro usando somente a variância intra-individual. O achado mais importante foi a necessidade de 14 replicações para meninos e homens, 15 para meninas e 23 para mulheres quando se deseja uma precisão de 90% na estimativa do consumo de energia. São necessárias 4 replicações para meninos e 7 para homens, meninas e mulheres para categorizar o consumo de energia considerando coeficiente de correlação de 0,9. Devido à variância intra-individual do consumo alimentar é necessário maior número de replicações de inquéritos dietéticos para estimar o consumo usual do que para classificar os indivíduos segundo o consumo alimentar.